A Robust Tool for Monitoring and Synchronizing Smart Grid through Adaptive Comb Filter - Pandiyan Murugesan; S Prabakaran (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
The power system signals are often polluted with harmonics and noise as a result of nonlinear load. This non stationary signal has to be monitored carefuly before it propagates as a grid problem.This article describes the design of adaptive comb filter, extraction of amplitude, frequency and phase with respect to time for monitoring purpose and extraction of harmonic components for suppressing the contamination present in the signal for synchronization with smart grid. The adaptive comb filter algorithm is a synchronizing tool implemented in Matlab/Simulink environment.The response of the filter is compared with enhanced phased locked loop to describe the characteristics of adaptive comb filter.The algorithm tracks the transient (dynamic) and steady state behaviour of the signal effectively, efficiently and accurately.